Comparison of six weeks eccentric overload training between bilateral and unilateral squat in basketball players - José Luis Hernández Davó; Pedro Monteagudo Jiménez; Rafael Sabido Solana (Asociación Española de Ciencias del Deporte, 2018)
Basketball is a team sport in which strength and power in the lower limb are key variables. The use of eccentric overload devices has augmented in the past years, and several studies have shown the benefits of this methodology to improve physical parameters. The aim of the present study is to compare the effects of bilateral and unilateral squat during eccentric overload training. Ten players from a same team participated in a six weeks of two session per week eccentric overload training. Participants were divided in two groups according to their performance in pretest. Test measured in pre and postest situation were a power test in flywheel, CMJ, triple hop test and T-Test. Training consisted in 4 sets of 8 repetitions of bilateral or unilateral squat. After treatment both groups improve their performance in T-Test and power test in flywheel device. Trends of improve were observed for triple hop test, with a greater ES for unilateral group. Results shown as eccentric overload training of bilateral or unilateral squat can be a good choice to improve physical performance, with different benefits according to the type of execution.